A case report of glucose transporter 1 deficiency syndrome with growth hormone deficiency diagnosed before starting ketogenic diet - Gianluca Tornese; Giuseppa Patti; Maria Chiara Pellegrin; Paola Costa; Flavio Faletra; Elena Faleschini; Egidio Barbi (BMC, 2020)
Abstract Background Growth failure and growth hormone deficiency (GHD) have been reported as one accessory feature of GLUT1 deficiency syndrome (GLUT1DS), considered so far as a long-term adverse effects of ketogenic diet which is used to treat this condition. Case presentation We report the case of a 10-year-old Caucasian boy referred for short stature (height − 2.56 SDS) and delayed growth (growth velocity − 4.33 SDS) who was diagnosed with GHD and started treatment with recombinant human growth hormone (rhGH). Because of his history of seizures with infantile onset, deceleration of head growth with microcephaly, ataxia, and moderate intellectual disability, a lumbar puncture was performed, which revealed a low CSF glucose concentration with a very low CSF-to-blood glucose ratio (< 0.4), and genetic tests detected a SLC2A1 gene exon 1 deletion confirming a diagnosis of GLUT1DS. Ketogenic diet was started. After 5.5 years of rhGH treatment his height was normalized (− 1.15 SDS). No side effects were reported during treatment, particularly on glycemic metabolism. Conclusions This is the first case of GHD in a Caucasian boy with GLUT1DS diagnosed before starting ketogenic diet, with a good response to rhGH treatment and absence of side effects. We speculate that GHD may represent a poorly recognized clinical feature of GLUT1DS rather than a complication due to ketogenic diet. Under-diagnosis may derive from the fact that growth failure is usually ascribed to ketogenic diet and therefore not further investigated. Pediatric neurologists need to be alerted to the possible presence of GHD in patients with GLUT1DS with slow growth, while pediatric endocrinologist need to refer GHD patients with additional features (motor and cognitive developmental delay, seizures with infantile onset, deceleration of head growth with acquired microcephaly, movement disorder with ataxia, dystonia, and spasticity) that may suggest GLUT1DS.